The invention of the psychosocial: An introduction - Hayward, R (History of the human sciences, 2012)
PMCID: PMC3627511This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited